Within- and among-population variation in chytridiomycosis-induced mortality in the toad Alytes obstetricans. - Ursina Tobler; Benedikt R Schmidt (PLoS ONE, 2010)
Chytridiomycosis is a fungal disease linked to local and global extinctions of amphibians. Susceptibility to chytridiomycosis varies greatly between amphibian species, but little is known about between- and within-population variability. However, this kind of variability is the basis for the evolution of tolerance and resistance evolution to disease.In a common garden experiment, we measured mortality after metamorphosis of Alytes obstetricans naturally infected with Batrachochytrium dendrobatidis. Mortality rates differed significantly among populations and ranged from 27 to 90%. Within populations, mortality strongly depended on mass at and time through metamorphosis.Although we cannot rule out that the differences observed resulted from differences in skin microbiota, different pathogen strains or environmental effects experienced by the host or the pathogen prior to the start of the experiment, we argue that genetic differences between populations are a likely source of at least part of this variation. To our knowledge, this is the first study showing differences in survival between and within populations under constant laboratory conditions. Assuming that some of this intraspecific variation has a genetic basis, this may suggest that there is the potential for the evolution of resistance or tolerance, which might allow population persistence.